Peningkatan Produktivitas Perawatan Mesin Polisher dengan Penerapan TPM menggunakan Metode OEE di PB. Surya Agung - Ayuningtyas, Dewi; Wahyudin, Wahyudin; Herwanto, Dene (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The purpose of this study was to analyze the effectiveness of the polisher machine using the Overall Equipment Effectiveness (OEE) method at PB. Surya Agung. The methods used in this study are the Pareto diagram and the cause-and-effect diagram (fishbone). The results of this study found that at PB. Surya Agung with the six big Loss method, six losses were obtained, including breakdown Loss, Setup and Adjustment Loss, idling and Minor Stoppage, Reduce Speed Loss, Defect Loss, Yield / Scrap Loss. The results of data processing obtained an average Overall Equipment Effectiveness value for 7 months in the period from January to July 2023 obtained a value of 65%, this value has not reached the Japan Institute of Plant Maintenance standard. The factor that has the largest percentage of the Six Big Losses factor on the polisher machine is Reduce Speed Losses with a value of 27%. which causes a decrease in machine effectiveness, this is because the machine / equipment and humans have not implemented the Total Productive Maintenance (TPM) concept.